2016
DOI: 10.14303/er.2016.127
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Stress among Public Secondary School Female Principals in Kenya: A case study of Rachuonyo North and Homa Bay Sub-Counties

Abstract: Principals play a pivotal role in performance of students in secondary schools. In many instances, this calls for high professional and societal demands, and expectations. As a result, principals experience stress. Studies in countries like USA, Britain, Norway, India, Nigeria and Kenya have revealed that optimal stress among principals enhances students' performance in public examinations while excessive stress reduces students' performance. In Rachuonyo North and Homa Bay Sub counties, the mean scores for sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…School heads perform important duties that are supposed to contribute to a successful outcome in schools (Juma, Simatwa &Ayodo, 2016;Wallace Foundation, 2013). However, the incidence of job stress has caused some heads to have low job satisfaction (Markow, Macia &Lee, 2013), others to lose interest in the job (Mbibi, Oluchi & Nwamuo., 2013) and some to opt for other occupations (Yambo, Kindiki &Tuitoek, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…School heads perform important duties that are supposed to contribute to a successful outcome in schools (Juma, Simatwa &Ayodo, 2016;Wallace Foundation, 2013). However, the incidence of job stress has caused some heads to have low job satisfaction (Markow, Macia &Lee, 2013), others to lose interest in the job (Mbibi, Oluchi & Nwamuo., 2013) and some to opt for other occupations (Yambo, Kindiki &Tuitoek, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The SES promotes sharing of social norms and values required for students to succeed in schools through social capital. It is suggested that socioeconomic indicators such as parents' highest education level, parents' highest occupation level, family income and size are important determinants of achievement (Chevalier & Lanot, 2002;Juma et al, 2012;Şirin, 2005;Tomul & Savasci, 2012).…”
Section: Family-related Factors and Achievementmentioning
confidence: 99%
“…Parents' highest education level and family income are suggested to be the long-term determinants of achievement and specifically the parental education level is the most important reason for the difference in student achievement (Chevalier & Lanot, 2002). It is remarked that the increase in family income leads to school achievement at every level of education (Juma et al, 2012) and generally the children of poor family have lower achievement (Chevalier & Lanot, 2002). According to Kyriakides et al (2019), the low family income, on the one hand, prevents students from living in a more developed settlement area, possessing a good peer group and accessing a school that provides a good education.…”
Section: Family-related Factors and Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…African scholars have also pinpointed socio-cultural constraints that bear upon female principals and teachers when they do exercise leadership in schools (Grant, 2005;Juma et al, 2011;Mestry & Schmidt, 2012;Omboko & Oyoo, 2011;Parsaloi & Steyn, 2013). Finally, this body of scholarship has both portrayed and contrasted uniquely 'female ways of leading' schools in different African societies including Ghana (Agezo & Hope, 2011;Kwadzo, 2010), Tanzania (Dady, 2014), Zimbabwe (Chabaya et al, 2009;Makura, 2012;, Kenya (Wambura, 2010), Nigeria (Ikoya, 2009), and South Africa (Lumby & Azaola, 2014;Mogadime et al, 2010;Naidoo et al, 2012;Smit, 2013).…”
Section: Introductionmentioning
confidence: 99%